2012
DOI: 10.1242/jeb.059626
|View full text |Cite
|
Sign up to set email alerts
|

Long-term memory and response generalization in mushroom body extrinsic neurons in the honeybee Apis mellifera

Abstract: SUMMARYHoneybees learn to associate an odor with sucrose reward under conditions that allow the monitoring of neural activity by imaging Ca 2+ transients in morphologically identified neurons. Here we report such recordings from mushroom body extrinsic neurons -which belong to a recurrent tract connecting the output of the mushroom body with its input, potentially providing inhibitory feedback -and other extrinsic neurons. The neuronsʼ responses to the learned odor and two novel control odors were measured 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…GABAergic “feedback neurons” that connect subregions of the MB lobes and calyces, and whose processes in the lobes appear to be post-synaptic, are also been seen in other insects including honeybee or the moth Manduca , where there are about 50 or 150, respectively (Homberg et al, 1987; Grünewald, 1999a), rather than just one as in Drosophila . The honeybee feedback neurons respond to various sensory stimuli via input from the MB lobes, and their activity can be influenced by learning (Grünewald, 1999b; Haehnel and Menzel, 2010, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…GABAergic “feedback neurons” that connect subregions of the MB lobes and calyces, and whose processes in the lobes appear to be post-synaptic, are also been seen in other insects including honeybee or the moth Manduca , where there are about 50 or 150, respectively (Homberg et al, 1987; Grünewald, 1999a), rather than just one as in Drosophila . The honeybee feedback neurons respond to various sensory stimuli via input from the MB lobes, and their activity can be influenced by learning (Grünewald, 1999b; Haehnel and Menzel, 2010, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The MB is known to be involved in learning, memory formation, and memory retrieval in the honeybee (Menzel et al, 2006) and Drosophila (Davis, 2011), and it can be expected that extrinsic neurons provide a readout of the learned induced neural restructuring within the MB. The MB ␤ neurons have been recorded several times in the past and were found to change their response properties during olfactory conditioning (Mauelshagen, 1993;Grunewald, 1999;Okada et al, 2007;Haehnel andMenzel, 2010, 2012;Strube-Bloss et al, 2011). Simple differential conditioning experiments uncovered several associative phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on MBONs (receiving convergent inputs from many KCs) have revealed important insights on information processing properties of MB such as multisensory convergence, temporal coding properties, learning-induced changes in MBON activity and stimulus categorization by multisensory MBONs [106,109,110]. Intracellular recordings from individual neurons within a specific group of GABAergic feedback neurons (A3 PCT neurons, a specific group of MBONs forming recurrent circuits from the MB lobes to the MB-calyx input) has highlighted the role of these neurons in mediating memory-related changes from the MB output to the MB-calyx input [22,58,59,93,111]. Physiological recordings from KCs, so far, have been mostly limited to the calcium imaging of spatial activation patterns, which has revealed important insights into experience-related changes in spatial activation patterns of pre-and postsynaptic elements in MB-calyx MG [21,23,112].…”
Section: New Approaches and Methodological Advancesmentioning
confidence: 99%